Clomiphene based ovarian stimulation in a commercial donor program - Shruti Gupta; Ruma Satwik; Abha Majumdar; Shweta Mittal; Neeti Tiwari (Wolters Kluwer Medknow Publications, 2015)
OBJECTIVE: This study was conducted to compare an extended clomiphene-based ovarian stimulation regimen with the conventional antagonist protocol in donor-recipient cycles. MATERIALS AND METHODS: A total of 170 (N) donors were stimulated between January 2013 and December 2013. Conventional antagonist protocol (group I) was employed in (n1 = 31) cycles, and clomiphene was used in (n2 = 139) donor cycles (group II). 50 mg clomiphene was given simultaneously with gonadotropins from day 2 of the cycle until the day of trigger. The analysis was performed retrospectively for oocytes retrieved, fertilization rates, cycle cancelation, blastocyst formation, and pregnancy rates. The dosages, cost, and terminal E2 (estradiol) were also compared between the two groups. RESULTS: The donor age groups were comparable in both the groups. There were no unsuccessful egg retrievals with clomiphene. The pregnancy rate (positive beta human chorionic gonadotropin) was significantly higher in the clomiphene group (odds ratio: 2.453; P = 0.02). Similarly, fertilization rate was significantly higher in the clomiphene group (59.5/50.5, P = 0.04). Eggs retrieved were similar in both groups, but the terminal E2 was significantly higher in the clomiphene group (P = 0.001). Average gonadotropin used was also significantly lower in clomiphene group (P < 0.001). CONCLUSION: Clomiphene can effectively prevent luteinizing hormone surge and limit the dose of gonadotropins thus bringing down the costs and its negative impact on the endometrium and oocyte quality.